The legacy of Hicks : his contribution to economic analysis - Hagemann, Harald; Hamouda, O. F.; Hicks, John, 1904-1989 (Routledge, 1994)
Sir John Hicks made a major contribution to almost every aspect of modern economic theory. His diverse and inventive work has left a huge impression on the discipline. Contributors: Christopher Bliss, Oxford University; John S. Chipman, University of Minnesota; Nicholas Georgescu-Roegen, Vanderbilt University; Richard Goodwin, University of Siena; Frank H. Hahn, Cambridge University; John D. Hey, University of York; Charles M. Kennedy, University of Kent; David Laidler, University of Western Ontario; Axel Leijonhufvud, University of California, Los Angeles; Robin C.O. Matthews, Cambridge Univ.